2014
DOI: 10.1002/lary.24896
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ossiculoplasty with titanium total ossicular replacement prosthesis

Abstract: Titanium TORPs offer children an effective method of ossicular reconstruction, with infrequent extrusion at least in the short term. The hearing improvement achieved in the early postoperative period appears to be maintained over the first year but may not be sustained over longer time periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
1
6
1
2
Order By: Relevance
“…7,[13][14][15][16][17][18][19][20][21][22][23][24] Similarly, achievement of an ABG 20 dB in 67.1% of cases falls within the range of reported rates (45.8%-81.4%). 7,[17][18][19][20][21][23][24][25] Our group previously published a study regarding short-term hearing outcomes of titanium ossiculoplasty. This earlier study reported better hearing outcomes with a mean postoperative ABG of 15.4 dB and achievement of an ABG 20 dB in 77.1% of cases.…”
Section: Short-term Outcomesmentioning
confidence: 95%
“…7,[13][14][15][16][17][18][19][20][21][22][23][24] Similarly, achievement of an ABG 20 dB in 67.1% of cases falls within the range of reported rates (45.8%-81.4%). 7,[17][18][19][20][21][23][24][25] Our group previously published a study regarding short-term hearing outcomes of titanium ossiculoplasty. This earlier study reported better hearing outcomes with a mean postoperative ABG of 15.4 dB and achievement of an ABG 20 dB in 77.1% of cases.…”
Section: Short-term Outcomesmentioning
confidence: 95%
“…[1][2][3][4][5][6] Despite the significant improvement that is often noted in postoperative hearing, the success of primary ossiculoplasty, defined as achievement of an air-bone gap (ABG) 20 dB, remains between 33% and 81% for all age groups and various prosthesis materials. 1,[6][7][8][9][10][11][12][13][14][15] When only titanium prostheses are analyzed, the success rate ranges between 46% and 81%. 1,[6][7][8][9][10][11][12][13][14] Furthermore, most studies report revision rates ranging between 10% and 20% for either functional failures or disease recurrence, highlighting the not uncommon need for a second surgery.…”
mentioning
confidence: 99%
“…1,[6][7][8][9][10][11][12][13][14][15] When only titanium prostheses are analyzed, the success rate ranges between 46% and 81%. 1,[6][7][8][9][10][11][12][13][14] Furthermore, most studies report revision rates ranging between 10% and 20% for either functional failures or disease recurrence, highlighting the not uncommon need for a second surgery. 8,16 Outcomes after revision surgery are thought to be worse than with primary surgery, although current objective data regarding the success of revision ossiculoplasty are limited in terms of variable analyses and success rates.…”
mentioning
confidence: 99%
“…En l'absence de recommandation consensuelle, les résultats de l'ossiculoplastie sont rapportés sans uniformité. Les séries de Nevoux J. et al [15], Quesnel S. et al [18], Wolter N.E et al [19], Murphy T.P et al [8], Michael P. et al [9] illustrent cette diversité en otologie pédiatrique. Les révisions chirurgicales pour récidive ou résiduel de la maladie cholestéatomateuse sont parfois incluses dans le recueil, ce qui peut induire un biais.…”
Section: Discussionunclassified
“…Wolter N.E. et al [19] ont aussi observé cette dégradation à long terme dans une série de 71 cas: 40% avaient une CA≤30 dB à 32 mois alors que le taux était de 60% à 2 mois de l'intervention.…”
Section: Discussionunclassified